Long-Term Dynamics of Voluntary Engagement: Differentiating Social Structural from Cohort and Period Effects - Jannes Jacobsen; David Schieferdecker; Denis Gerstorf; Swen Hutter; Jule Specht (VOLUNTAS: International Journal of Voluntary and Nonprofit Organizations, 2022)
Prior research has suggested three explanations why levels of voluntary engagement rise and fall over time within societies. A social structural explanation considers individual resources crucial for engagement and argues that a redistribution of those resources may bring about changes in engagement. A cohort-based explanation considers socialisation and experiences in formative years as crucial for the uptake of engagement. Finally, a period-based explanation considers extraordinary events, external shocks, and crises to be crucial for engagement. So far, these explanations have mainly been tested separately and little is known about the relative strength of each of the proposed factors. Using data from a large German household panel survey that assessed engagement almost annually across four decades, we found that most social structural factors (e.g., education, employment, income) maintained their predictive effects for engagement, irrespective of cohort or period. The only notable exception was that the gender gap observed has narrowed substantially across periods and cohorts. Moreover, cohort effects were rendered almost negligible once we factored in periods. Taken together, our results suggest that individual characteristics and extraordinary events are the main factors influencing voluntary engagement rather than shared societal experiences of cohorts.
Keywords: 320; civil society; social participation; political participation; longitudinal analyses; gender differences; SOEP